The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/j.clim.2016.06.017
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of neutrophils to CNS autoimmunity

Abstract: Multiple sclerosis (MS) is believed to be initiated when myelin-specific T cells infiltrate the central nervous system (CNS), triggering subsequent recruitment of inflammatory leukocytes to the CNS. The contribution of neutrophils to CNS autoimmune disease has been underappreciated, but several studies in experimental autoimmune encephalomyelitis (EAE), an animal model of MS, indicate that neutrophils have an important role in inflammation. Neutrophils are hypothesized to contribute to the pathogenesis of EAE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
79
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 64 publications
(123 reference statements)
8
79
0
Order By: Relevance
“…Whereas the numbers of Th17 effector T cells were slightly increased in Cup and EAE mice, there was a significant induction in Cup/EAE mice (Figure 3f). As flow cytometry revealed a higher number of neutrophils in Cup/EAE animals, and other studies in EAE indicate that neutrophils have an important role in inflammation (Y Liu et al, 2015;Pierson, Wagner, & Goverman, 2016),. we examined ultrastructural as well as enzymatically stained images to identify neutrophils in perivascular infiltrates(Figure 3g).…”
supporting
confidence: 52%
See 1 more Smart Citation
“…Whereas the numbers of Th17 effector T cells were slightly increased in Cup and EAE mice, there was a significant induction in Cup/EAE mice (Figure 3f). As flow cytometry revealed a higher number of neutrophils in Cup/EAE animals, and other studies in EAE indicate that neutrophils have an important role in inflammation (Y Liu et al, 2015;Pierson, Wagner, & Goverman, 2016),. we examined ultrastructural as well as enzymatically stained images to identify neutrophils in perivascular infiltrates(Figure 3g).…”
supporting
confidence: 52%
“…Whereas the numbers of Th17 effector T cells were slightly increased in Cup and EAE mice, there was a significant induction in Cup/EAE mice (Figure f). As flow cytometry revealed a higher number of neutrophils in Cup/EAE animals, and other studies in EAE indicate that neutrophils have an important role in inflammation (Y. Liu et al, ; Pierson, Wagner, & Goverman, ), we examined ultrastructural as well as enzymatically stained images to identify neutrophils in perivascular infiltrates (Figure g). Using both techniques, high numbers of neutrophils were found in the perivascular compartment and in the forebrain parenchyma, with densities ranging from 1,778 to 12,526 cells/mm 2 (mean, 4,614 ± 359 granulocytes/mm 2 ) in the proximity of perivascular forebrain lesions.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, CXCL5, a neutrophil chemotactic protein and one of the most up‐regulated chemokines secreted by activated astrocytes in this study, was recently reported to be a serum biomarker associated with multiple sclerosis relapse (Rumble et al, ), and was elevated in cerebrospinal fluid samples of patients experiencing relapse compared to those in remission (Blackmore et al, ). Neutrophils have garnered attention for their involvement in EAE (Pierson, Wagner, & Goverman, ), ability to facilitate demyelination(Bell et al, ; Ferrari et al, ; Liu et al, ) Ferrari et al, ; Bell et al, ) and promote neurodegeneration (Zenaro et al, ). Indeed, neutrophil accumulation in the brain during experimental autoimmune encephalomyelitis (EAE) appears to underlie ‘atypical’ signs of disease characterized by clinical appearance of hunching, head tilt, ataxia, axial rotation and spinning (Yan, Yang, & Parkitny, ), which contrasts the traditional disease symptoms that are characterized by ascending paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies in both MS patients and EAE mice suggest a critical role for neutrophils in disease pathogenesis. 10,11 Neutrophils in the blood of MS patients exhibit a primed phenotype, and both neutrophil number and biomarkers of neutrophil activity increase during relapses. 11 In EAE, neutrophils comprise a significant percentage of CNS-infiltrating leukocytes prior to disease onset and relapse, and disease was ameliorated when neutrophils were depleted prior to, but not after, disease onset or relapse, suggesting important neutrophil function during the initial formation of MS lesions.…”
Section: Introductionmentioning
confidence: 99%